Femtosecond laser inscribed bridging cladding waveguides combining single- and multi-core optical fibres for shape sensing - Kalli, Kyriacos; Theodosiou, Antreas; Stojanovic, Stefan; Ioannou, Andreas (My University, 2019)
We show that femtosecond laser inscribed “bridging waveguides” can couple the displaced cores of different types of optical fibres. We explore coupling between single- and four-core fibre, incorporating multiple Bragg gratings. The sensor is calibrated for bend and shape sensing.
Keywords: Femtosecond laser inscription; fibre Bragg gratings; optical sensing; shape sensing